(untitled) (Bangladesh Pharmaceutical Journal, 2016)
The seeds of Helianthus annuus have been investigated for the presence of various chemical components and biological activities with special emphasis to the anti-oxidant, antimicrobial, cytotoxic and thrombolytic assay. The results of standard phytochemical analysis revealed the presence of tannins, saponins, flavonoids, carbohydrates, steroids, fixed oils and vitamins. In vitro antioxidant activity of methanolic seed extract of H. annuus was determined by DPPH free radical scavenging assay, which demonstrated very significant antioxidant potential compared to standard antioxidant (ascorbic acid). In case of antimicrobial assay, the methanolic and ethyl acetate extract of H. annuus seeds showed high sensitivity to Salmonella typhi and moderate sensitivity to Pseudomonous aeuregenosa. The petroleum ether extract revealed high sensitivity to P. aeuregenosa. The methanolic extract of H. annuus displayed LC50 1.2 ug/ml and its petroleum ether extract showed LC50 of 1.1 ug/ml, which indicated significant cytotoxicity. Bangladesh Pharmaceutical Journal 19(1): 100-105, 2016